DARING SUSTAINABLE ROAD TRANSPORT POLICIES IN WEST AFRICA: BETWEEN CHALLENGES AND NECESSITY - (:unkn) unknown (My University, 2022)
West Africa is experiencing growing urbanization which necessarily leads to many needs in terms of road transport in cities. However, according to the report of the Intergovernmental Panel on Climate Change, transport is responsible for a large part of the carbon dioxide (CO2) emissions which contribute strongly to the phenomenon of current climate variability. This article therefore aims to identify the importance of a reflection on the promotion of sustainable urban transport policy in West Africa. This theoretical contribution presents the arguments (the poverty of the populations and the low share of responsibility of the countries of the region in the current global warming) that can come up against such a project. It also shows that despite these arguments, it is currently wise to advocate sustainable transport policies in the cities of the region because these countries undoubtedly have their share of responsibility in this global concern on the link between transport and environmental problems. Indeed, these countries are increasingly characterized by an increase in their needs in terms of the use of energy sources in road transport, the insufficiency of public transport, the obsolescence of their vehicle fleet which is accompanied by the use of often poor quality fossil fuels and air pollution in urban areas.
Keywords: African Research